2019
DOI: 10.1177/0960327119871093
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-disulfide homeostasis and ischemia-modified albumin levels as indicators of oxidative stress in welders’ lung disease

Abstract: Welders’ lung disease refers to mixed exposure to different kinds of metals and chemicals from welding fumes, which affect all parts of the respiratory tract including airways and parenchyma together. This study aimed to investigate the oxidative status in patients with welders’ lung (PWL) by means of thiol-disulfide homeostasis and ischemia-modified albumin (IMA) levels. The male welder workers diagnosed with welders’ lung disease and healthy individuals were recruited in the study. Plasma levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…They also found a signi cant decrease in the activity of catalase (CAT) in workers with lung disease compared to controls. These results indicate the importance of oxidative stress in the pathogenesis of Welder's lung disease (17). Graczyk et al (2016) carried outa human study on the welding fume impacts on 20 non-smoking workers.…”
Section: Discussionmentioning
confidence: 89%
“…They also found a signi cant decrease in the activity of catalase (CAT) in workers with lung disease compared to controls. These results indicate the importance of oxidative stress in the pathogenesis of Welder's lung disease (17). Graczyk et al (2016) carried outa human study on the welding fume impacts on 20 non-smoking workers.…”
Section: Discussionmentioning
confidence: 89%
“…Under OS conditions, the thiol groups of the aminoacids with sulphur groups such as cysteine and methionine form reversible disulphide bonds with the low molecular weight thiol groups. This is known as dynamic TDH and has been investigated in several diseases such as Graves' disease (Agan et al, 2019), childhood iron deficiency anemia (Topal, et al, 2019), Welders' lung disease (Karatas et al, 2019) stage were found to be significantly lower than the lower stage patients. In contrast, ARES levels were found to correlate with nuclear grade in renal cell carcinoma patients (Aldemir et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An intensity of this process is predetermined by amino acid composition of proteins and could be considered as an early marker of oxidative stress. The degree of oxidative modification of albumin can be estimated by the concentration of mercaptalbumin and non-mercaptalbumin or their ratio, or by determination of albumin ability to bind cobalt iones (Albumin Cobalt Binding Test) [46,47]. However, both of these methods do not give the information about the conformational changes in this protein in response to the oxidation process.…”
Section: Discussionmentioning
confidence: 99%